HawkRadon - Saraiva, A. P.; Lourenço, A. M.; Soares, B.; Monteiro, D.; Grilo, D.; Saraiva, T. (Open Schools Journal for Open Science, 2020)
In this project, the students decided to measure the values of radon in the water and in the air in different points of our city and, at the same time, warn people about the consequences of high values. We placed several detectors to measure the values of radon concentrations and concluded that some of the values were well above the reference values. The project was only possible due to the unconditional help of the city council of Pinhel, the LabExpoRad of Beira Interior University and the students that attended our school last year. We think that this work represents a school open to an open society.